Knowledge, attitudes and practices on healthy eating in adolescents of two Public Educational Institutions, Lima East-2018 - Yanina Fustamante Ticlla (2019)
Objective: Determine the level of knowledge, attitudes and practices on healthy eating in adolescents fromtwo educational institutions. Methodology: Is non-experimental design, cross-sectional, and descriptivetype. The population was made up of all the students of the 1st and 5th grade of the secondary level.The sample consisted of 589 students. The instrument was an applied questionnaire of 42 questions,knowledge, attitudes and practices. Results: It was found that 57% of adolescents have a regular level ofknowledge, 83.4% have a favorable attitude and 78.2% of adolescents presented an inadequate practicein healthy eating. Conclusions: More than half of adolescents have a level of regular knowledge. On theother hand, it was found that they presented a favorable attitude in opting for a healthy diet. However, thelargest proportion do not practice it adequately.